Âncoras de carreiras de jornalistas que atuam em grandes grupos de comunicação impressa: o caso do Estadão - Mortara, Felipe (2015)
This research project identified relationships between career anchors and the activities of journalists that work in a large printing media company in Brazil. Through the analysis of a case study with 56 journalists from Grupo Estado editorial office, the survey focused on how the journalists perform and adapt their careers in an increasingly transforming scenario, under the influence of new technologies and media convergence. Life style and autonomy and independence were the prevalent carrer anchors found among editors and reporters. It was observed that not only reporters with this profile have better chances to become editors but the latter will have preference for hiring reporters with similar career anchors. Also, at least within this case study, to verify elements that include journalists within boundaryless and protean careers were observed